2007
DOI: 10.1007/s10461-007-9293-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Social Preparedness for Antiretroviral Therapy in a Generalized AIDS Epidemic: A Diffusion of Innovations Approach

Abstract: Researchers conducted focus groups in the Eastern Cape Province of South Africa concerning AIDS and treatment options. Constituent groups included adults aged 25-45, HIV/AIDS caregivers, HIV-positive adults, nurses, rural elders, teenagers, and traditional healers. This pilot work aimed to gather early evidence on perceptions about the government's rollout of antiretroviral treatment (ART), identify potential barriers to success, and inform a subsequent pilot survey. Diffusion of innovations theory was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Thirty relevant studies were identified, of which 11 were in peerreviewed journals [15][16][17][18][19][20][21][22][23][24][25] and 19 were in conference abstracts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty relevant studies were identified, of which 11 were in peerreviewed journals [15][16][17][18][19][20][21][22][23][24][25] and 19 were in conference abstracts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 30 studies, 21 were from Africa,* 6 from east/southeast Asia,The data collection methods described in the papers comprised mostly of interviews (22 studies), y surveys (7 studies), 16,27,29,34,39,40,42 review of clinical data (7 studies), 18,20,22,27,31,36,38 and focus-group discussions (6 studies). 21,23,28,32,42,43 Respondents included PLWHA with/without ART (22 studies), z noninfected people including elders, teenagers, and university students (11 studies), § health care workers including nurses, doctors, social workers, laboratory technologists (7 studies), 15,21,25,28,30,42,43 family members and/or friends of PLWHA (5 studies), 17,19,21,25,43 traditional healers (1 study), 21 and representatives of nongovernmental and community-based organizations (NGOs and CBOs; 1 study).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations